Hubungan Kualitas Tidur Dengan Kejadian Hipertensi Pada Lansia Di Panti Perlindungan Sosial Tresna Werdha Provinsi Jawa Barat - Devi Ratnasari; Eti Suliyawati; Aji Lasmana; Andri Nugraha (Journal of Health (JoH), 2019)
Sleep is a basic human need that must be fulfilled. As you get older the quality of one's sleep will decrease. Sleep quality is a measure where a person can easily start sleeping, can maintain a state of sleep and get adequate REM and NREM sleep stages. Poor sleep quality can increase the risk of hypertension, heart disease, and other medical conditions. Hypertension is the main risk factor for cardiovascular disease and is known as the silent killer because it is asymptomatic. The purpose of this study was to determine the relationship between sleep quality and the incidence of hypertension in the elderly. The type of research used was correlative with a case control approach, the sampling technique was purposive sampling with 74 elderly people divided into control groups and case groups. Data collection uses PSQI (Pittsburgh Sleep Quality Index) and medical records, then analyzed by Chi-square. The results showed that there was a correlation between sleep quality and the incidence of hypertension in the elderly at the Tresna Werdha Social Institution in West Java Province (p = 0.047, p <0.05) with a low closeness rate of 0.225. Health workers are expected to be able to provide information about the factors that influence the incidence of hypertension and make efforts that can improve sleep quality in the elderly.